Discursive constitutionalism - Bui, NS (University of Chicago Law School, 2023)
“Constitutionalism” has been contentiously debated at national and international levels. This Article develops the concept of discursive constitutionalism, defined as the construction of constitutionalism through public discourse. It theorizes about four elements (ideas, actors, actions, and spaces) and the constructive logic of discursive constitutionalism. Public constitutionalist discourse can be shaped by the existing relations of political power. At the same time, it can constrain the political monopoly of constitutional thinking, shape the design of institutions to limit political power, and prevent the arbitrary use of political power in practice. This study provides an explanatory account of three models of discursive constitutionalism in East Asia. The protectionist model in Japan refers to the discursive defense of national constitutional commitments to international peace and renouncing war. The reformist model in China denotes the discursive promotion of institutional reforms in line with normative values of constitutionalism. The diffusionist model in Vietnam features the discursive spread of constitutionalist ideas from external international and comparative sources into internal intellectual communities. Discursive constitutionalism can be a useful conceptual tool to understand the quest for constitutionalism through public discourse.